EFEKTIVITAS PENGELOLAAN PIUTANG PASIEN BPJS (Studi Kasus pada RSUD Dr. Saiful Anwar Malang) - Ricatur R.N, Devi; Wijayanti, Anita (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aimed to determine the effectiveness of the management of patient accounts BPJS contained in Hospital Dr. Saiful Anwar Malang to see the management of receivables that have been implemented. And to examine the relationship receivable turnover rate BPJS patients with the effectiveness of cash flow as measured by the current ratio analysis. This research uses descriptive quantitative method that consists of variable accounts receivable turnover ratio, average collection of receivables as well as current ratio (current ratio).The results showed that the management accounts BPJS patients in Hospital Dr. Saiful Anwar Malang has been running effectively, but there are some things that should be fixed credit policy related to the completeness of the collection of documents dealing with verification of claims to the BPJS. This is done so that the collection of documents verifying the claims do not result in long-running collection of accounts receivable. Keywords: Accounts Receivable, Accounts Receivable Turnover Rate, Effective Cash Flow (Current Ratio)